Efficacy of salpingectomy at hysterectomy to reduce the risk of epithelial ovarian cancer: a systematic review. (May 2017) - Darelius, A; Lycke, M; Kindblom, JM; Kristjansdottir, B; Sundfeldt, K; Strandell, A
Abstract : Background: It has been argued that salpingectomy would reduce the risk of epithelial ovarian cancer (EOC), based on the theory of the tube being the site of origin. Objectives: To conduct a systematic review of 'salpingectomy' associated with ovarian cancer risk and 'salpingectomy with concomitant hysterectomy' on outcomes of complications including endocrine function. Search strategy: A comprehensive search was conducted in PubMed, Embase, and the Cochrane library. Selection criteria: Original studies and systematic reviews were eligible. Data collection and analysis: Each article was quality assessed. Data were extracted and, when possible, pooled in meta‐analyses. The certainty of evidence across studies was evaluated using GRADE. Main results: Of 844 articles found, 11 were included. No study evaluated risk reduction for EOC after salpingectomy in conjunction with hysterectomy. Two retrospective studies reported a reduced ovarian cancer risk after indicated salpingectomy, compared with no surgery: adjusted hazard ratio 0.65 (95% confidence interval, 95% CI 0.52–0.81) and adjusted odds ratio 0.58 (95% CI 0.36–0.95). Complications did not differ between groups with or without salpingectomy, but were non‐systematically reported. Ovarian endocrine function, measured with surrogate outcomes, did not differ at short‐term follow‐up in randomised or observational studies. The certainty of evidence was very low or low for all outcomes. Conclusions: There is currently insufficient evidence to state that opportunistic salpingectomy reduces the risk of EOC. The impact on long‐term endocrine function is unknown. The heterogeneity in results and identified knowledge gaps stress the need for a prospective trial. Tweetable abstract: Insufficient evidence for prophylactic removal of the fallopian tubes for risk reduction of ovarian cancer. Tweetable abstract: Insufficient evidence for prophylactic removal of the fallopian tubes for risk reduction of ovarian cancer.